2021
DOI: 10.20944/preprints202107.0110.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Multi-Criteria Assessment Strategy for 3d Printed Porous Polyetheretherketone (Peek) Patient-Specific Implants for Orbital Wall Reconstruction

Abstract: Pure orbital blowout fractures occur within the confines of the internal orbital wall. Restoration of orbital form and volume is paramount to prevent functional and esthetic impairment. The anatomical peculiarity of the orbit has encouraged surgeons to develop implants with customized features to restore its architecture. This has resulted in worldwide clinical demand for patient-specific implants (PSIs) designed to fit precisely in the patient's unique anatomy. Fused filament fabrication (FFF) three-dimension… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…PEEKs are highly biocompatible, durable, and fatigue resistant, but only a few studies have reported their use in orbital implant reconstruction. 14 The efficiency of PEEK PSIs was compared with that of prebent titanium implants in the reconstruction of posttraumatic orbital wall fractures. Postoperative diplopia was seen in 17.9% of patients treated with PEEK PSIs and 29.4% of patients with prebent implants.…”
Section: Overview Of the Traditional Approach To Acute Orbital Traumamentioning
confidence: 99%
“…PEEKs are highly biocompatible, durable, and fatigue resistant, but only a few studies have reported their use in orbital implant reconstruction. 14 The efficiency of PEEK PSIs was compared with that of prebent titanium implants in the reconstruction of posttraumatic orbital wall fractures. Postoperative diplopia was seen in 17.9% of patients treated with PEEK PSIs and 29.4% of patients with prebent implants.…”
Section: Overview Of the Traditional Approach To Acute Orbital Traumamentioning
confidence: 99%